Nodal beam stack vibration isolators. (1st November 2022) - Rai, George; Rahn, Christopher; Smith, Edward; Marr, Conor
Abstract: This paper introduces additively manufactured beam networks that isolate vibration with multiple broad bandgaps. The isolators consist of symmetric stacks of beams with tip masses connected in series via compliant hinges near nodal points. An analytical model is derived to predict the vibration behavior of a beam stack. An isolator with four beams is designed to provide a band gap of 32 Hz with a center frequency at 72 Hz. A Polylactic acid polymer prototype is 3D printed and the frequency response of input force to transmitted force is experimentally measured showing a large 41 Hz band gap with a center frequency also around 72 Hz. The experimentally validated model is used to design a 10 beam isolator with a low frequency band gap from 10 to 86 Hz, and a high frequency band gap from 202 to 543 Hz.